Overcoming reading disabilities among teenage students with learning disabilities through collaborative storybook intervention - Sanal, Seda Ozer; Erdem, Mukaddes (Springer, 2023)
Language develops, is shaped, and transmitted through interaction. Similarly, reading cannot be learned entirely and accurately in isolation from people. Based on the assumption that reading is supported through interactions, this study included the development of a collaborative storybook. It examined its effects on students' reading performance with learning disabilities (LD). The researchers constructed a collaborative storybook intervention (CSI) of 29 stories containing collaborative activities that support the reading skills of children with LD. Researchers wrote all 29 stories. Three students aged 13-14 with LD participated in the experimental process. A multiple-probes-across-behavior single-case experimental design was utilized to determine the effect of a collaborative storybook. The design is helpful to answer demonstrative type research questions where the skill or behavior may not be unlearned in a short period. Changes in the participants' reading rate, reading accuracy, and reading comprehension performances were examined. Effective teaching material that special education teachers can use with LD in students' reading processes has been revealed. Social validity data supported that CSI offered an effective intervention. Additionally, researchers in this study suggested that collaborative storybooks are an acceptable intervention for students with reading difficulties. The findings contributed to the knowledge on designing effective collaborative educational e-materials.
Keywords: Reading; Collaboration; Learning disability; Storybook; Single-case design